OPTIMIZATION OF PRESCHOOL AGE CHILDREN'S DEVELOPMENT THROUGH EARLY DETECTION OF CHILD DEVELOPMENT - Tunggul Sri Agus Setyaningsih; Hesti Wahyuni (JCES (Journal of Character Education Society), 2021)
Abstrak: Pelayanan kesehatan dengan stimulasi dan deteksi dini tumbuh kembang anak minimal dua kali dalam setahun dapat di gunakan sebagai salah satu indikator yang bisa menjadi ukuran keberhasilan upaya peningkatan kesehatan  balita dan anak usia prasekolah. Apabila gangguan perkembangan tidak ditangani dengan tepat, maka dapat berlanjut hingga remaja atau dewasa. Kegiatan pengabdian ini bertujuan untuk mengetahui perkembangan anak balita dan usia prasekolah melalui deteksi dini perkembangan anak. Metode yang di gunakan dengan melakukan penilaian pemeriksaan deteksi dini perkembangan anak, diawali dengan menyiapkan bahan pemeriksaan formulir KPSP (Kuesioner Pra Skrining Perkembangan), kemudian menginterpretasikan penilaian pemeriksaan deteksi dini perkembangan anak. Hasilnya rata-rata perkembangan anak sesuai (S) sebanyak 24 anak (82,75%), meskipun masih ada yang meragukan (M) sebanyak 5 anak (17, 25%). Dengan mengetahui perkembangan anak balita dan prasekolah maka upaya mencegah, menstimulasi, mendeteksi, dan mengintervensi sedini mungkin jika terjadi masalah dalam perkembangan, sehingga tercapai perkembangan anak yang optimal.Abstract: Health services with stimulation and early detection of children's growth and development at least twice a year can be used as an indicator that can measure the success of efforts to improve the health of toddlers and preschoolers. If there are developmental disorders that are not handled properly it can continue into adolescence or adulthood. This service activity aims to determine the development of toddlers and preschool children through early detection of child development. The method used is to conduct an assessment of early detection of child development, begins with preparing the examination material for the KPSP form (Developmental Pre-Screening Questionnaire), then interpreting the assessment for early detection of child development. The result is that the average child development according to (S) is 24 children (82.75%), although there is still doubt (M) as many as 5 children (17, 25%). By knowing the development of toddlers and preschool children, efforts to prevent, stimulate, detect, and intervene as early as possible if there are obstacles in their development, so that optimal child development is achieved.